FAKTOR PENYEBAB APARAT KEPOLISIAN TIDAK MENINDAK TEGAS SERTA UPAYA PENANGGULANGAN EKSPLOITASI ANAK OLEH ORANG TUA MENJADI PENJUAL MAKANAN DAN KORAN DI LAMPU MERAH ELTARI KOTA KUPANG - Pono, Yohanis Soni; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2023)
A child is a gift given by God Almighty from birth which has inherent dignity and worth as a human being which cannot be separated, increased or reduced. Children are also the next generation of the nation and have a role in ensuring the future progress of the nation and state. This research is empirical legal research carried out in Kupang City. Data collection techniques use interview and observation techniques. The data used are primary and secondary data. This research was conducted at the Kupang City and Eltari Police. The results of data processing were analyzed descriptively qualitatively. The results of this research show: (1) The police do not take firm action against parents who exploit children due to four factors, namely, legal factors, law enforcement factors, facility factors, and community factors. (2) Police efforts to exploit children by parents consist of pre-emptive efforts, preventive efforts and repressive efforts.